Enhanced phoxim biodegradation by immobilizing Novosphingobium sp. RL4 on attapulgite-sodium alginate - Peng, Tong; Huang, Yining; Yang, Tao; Wang, Yinquan; Jin, Ling (Frontiers in Microbiology, 2025)
BackgroundResidual phoxim pollution presents a potential threat to natural ecosystems and human health. The immobilization of degrading strains on natural adsorbent materials is a common strategy to enhance the degradation of target compounds in the environment by the strains.MethodsA phoxim-degrading bacterial strain was isolated from the rhizosphere soil of rhubarb (Rheum palmatum L.), which had been exposed to long-term phoxim contamination. To enhance its stability and practical applicability, sodium alginate (SA) was utilized as a carrier material, while biochar (BC) and attapulgite (ATP) served as adsorption materials. These components were used to immobilize the strain, forming three distinct bacterial bead formulations: SA-RL4, SA + BC-RL4, and SA + ATP-RL4.ResultsThe isolated phoxim-degrading strain was identified as Novosphingobium sp. RL4. Furthermore, the degradation products of phoxim by strain RL4 were analyzed and characterized. Based on the specific surface area, mass-transfer performance results, adsorption isotherms, and degradation efficiency, the addition of ATP or BC to SA has an equally positive impact on the degradation of phoxim by immobilized microspheres. ATP can replace BC as an adsorbent carrier material for embedding bacteria to a certain extent. At 20 mg/L, SA + ATP-RL4 degraded 89.37% of phoxim in 72 h. Importantly, SA + ATP-RL4 can be reused, and the degradation efficiency remained above 80% after 5 cycles. Furthermore, it exhibits high tolerance and better degradation ability compared to free cells of RL4 when used in treating agricultural wastewater containing phoxim.ConclusionSA + ATP-RL4 shows potential for in situ remediation of phoxim-contaminated environments.